A rare population of tumor antigen-specific CD4+CD8+ double-positive αβ T lymphocytes uniquely provide CD8-independent TCR genes for engineering therapeutic T cells. Issue 1 (9th January 2019) - Matsuzaki, Junko; Tsuji, Takemasa; Chodon, Thinle; Ryan, Courtney; Koya, Richard C.; Odunsi, Kunle
Abstract : Background: High-affinity tumor antigen-specific T-cell receptor (TCR) gene is required to engineer potent T cells for therapeutic treatment of cancer patients. However, discovery of suitable therapeutic TCR genes is hampered by the fact that naturally occurring tumor antigen-specific TCRs are generally of low-affinity, and artificial modification of TCRs can mediate cross-reactivity to other antigens expressed in normal tissues. Here, we discovered a naturally occurring T-cell clone which expressed high-affinity HLA-A*02:01 (A*02)-restricted TCR against NY-ESO-1 from a patient who had NY-ESO-1-expressing ovarian tumor. Methods: A*02-restricted NY-ESO-1-specific T-cell clones were established from peripheral blood of patients who had NY-ESO-1-expressing ovarian tumors. TCR α and β chain genes were retrovirally transduced into polyclonally activated T cells. Phenotype and function of the parental and TCR-transduced T cells were analyzed by flow cytometry, ELISA and cytotoxicity assay. In vivo therapeutic efficacy was investigated in a xenograft model using NOD/SCID/IL-2Rγ-deficient (NSG) mice. Results: A rare population of NY-ESO-1-specific T cells, which we named 19305DP, expressed cell surface CD4, CD8α, and CD8β but not CD56 and recognized A*02 + NY-ESO-1 + cancer cell lines in a CD4- and CD8-independent manner. 19305DP showed a gene expression profile that is consistent with a mixed profile of CD4 + and CD8 + single-positive T cells. Both CD4 + and CD8 + T cells that were retrovirally transduced with 19305DP-derived TCR gene (19305DP-TCR) showed strong reactivity against A*02 + NY-ESO-1 + cancer cells, whereas TCR genes from the conventional A*02-restricted NY-ESO-1-specific CD8 + single-positive T-cell clones functioned only in CD8 + T cells. Both 19305DP-TCR gene-engineered CD4 + and CD8 + T cells eliminated A*02 + NY-ESO-1 + tumor xenografts in NSG mice. Finally, based on reactivity against a series of alanine-substituted peptides and a panel of normal human tissue-derived primary cells, 19305DP-TCR was predicted to have no cross-reactivity against any human non-NY-ESO-1 proteins. Conclusion: Together, our results indicate that the naturally occurring 19305DP-TCR derived from CD4 + CD8 + double-positive αβ T cells, is a promising therapeutic TCR gene for effective and safe adoptive T-cell therapy in A*02 + patients with NY-ESO-1-expressing tumor.